"I Have Everything to Win and Nothing to Lose": Patient Experiences of Mobilization Out of Bed Immediately After Abdominal Surgery. Issue 12 (17th September 2020) - Svensson-Raskh, Anna; Schandl, Anna; Holdar, Ulrika; Fagevik Olsén, Monika; Nygren-Bonnier, Malin
Abstract: Objective: Early mobilization is advocated for patients going through abdominal surgery; however, little is known about the patient experience of being mobilized immediately after surgery. The purpose of this study was to explore patient experiences of mobilization immediately after elective abdominal cancer surgery. Methods: This interview study used qualitative content analysis. With the use of purposeful sampling, a total of 23 participants who had been mobilized immediately after abdominal surgery were recruited at a university hospital in Stockholm, Sweden. Individual face-to-face interviews were conducted within 1 to 4 days after surgery and took place at the surgical ward where the participants were treated. A semi-structured guide was used. All interviews were audio recorded and transcribed verbatim. Results: The content analysis revealed 3 categories that emerged into 1 overarching theme: "to do whatever it takes to get home earlier." The participants experienced that mobilization out of bed had an impact on their physical and mental well-being. Motivation and the experiences of themselves and others were factors that affected patient attitudes toward early mobilization. Preparation and competent caregivers were emphasized as important factors that enabled the patient to feel safe and confident during mobilization. Conclusions: Patients experienced mobilization as an important part of the care that had an impact on recovery and well-being, physically as well as mentally, both immediately and over time. Impact: As this is the first study to our knowledge to investigate patient experiences of mobilization immediately after abdominal surgery, this information can be used to support the development of early mobilization protocols in hospital settings.